Student independence in overcoming the impact of COVID-19: classical online guidance based on character values - Hera Heru Sri Suryanti; Sri Hartini; Ferisa Prasetyaning Utami (Jurnal Cakrawala Pendidikan, 2022)
Independence is an individual's ability to face, accept, and find solutions to solve problems without harming/incriminating other parties. The purpose of the study is to increase student independence in solving the problem of the impact of COVID-19 through online classical guidance based on character values. This research is experimental with a one-group pre-test-post-test experimental design. The research population was 190 FKIP students in Solo Raya. 48 samples were determined using purposive sampling, 20 students were selected from samples with low levels of independence. Data collection using self-reliance instrument questionnaires, observation, interviews, and documentation. Data analysis used non-parametric statistics with the Wilcoxon Signed Rank Test. The results showed that there was a significant difference in the pre-test and post-test scores of students' independence in overcoming the problem of the impact of COVID-19 obtained from the results of the Wilcoxon Signed Rank test, namely the value (p = 0.000) 0.05, which means online classical guidance is based on character values. can increase student independence by overcoming problems with the impact of COVID-19.